2019
DOI: 10.1093/ndt/gfz133
|View full text |Cite
|
Sign up to set email alerts
|

Valvular heart disease and calcification in CKD: more common than appreciated

Abstract: Ischaemic heart disease, sudden cardiac death and arrhythmias, heart failure, stroke and peripheral arterial disease make up >50% of the causes of death in advanced chronic kidney disease (CKD). Calcification of the vascular tree and heart valves is partially related to these complications and has received growing attention in the literature. However, the main focus of research has been on the pathophysiology and consequences of vascular calcification, with less attention being paid to valvular calcificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 61 publications
0
75
1
1
Order By: Relevance
“… 27 , 28 In addition to multiple traditional and emerging cardiovascular risk factors, the association of abnormal ABI with arrhythmia in chronic hemodialysis patients in the present study could be explained by the presence of valvular calcifications as reported by Ureña-Torres. 29 Although vascular access failure has been reported to be frequently associated with abnormal ABI in chronic hemodialysis patients, 30 the lack of association observed in the present study, where most patients used either temporary or permanent catheters, could be due to the small study sample size.…”
Section: Discussioncontrasting
confidence: 57%
“… 27 , 28 In addition to multiple traditional and emerging cardiovascular risk factors, the association of abnormal ABI with arrhythmia in chronic hemodialysis patients in the present study could be explained by the presence of valvular calcifications as reported by Ureña-Torres. 29 Although vascular access failure has been reported to be frequently associated with abnormal ABI in chronic hemodialysis patients, 30 the lack of association observed in the present study, where most patients used either temporary or permanent catheters, could be due to the small study sample size.…”
Section: Discussioncontrasting
confidence: 57%
“…As recently revised by Urena-Torres et al [29], multiple mechanisms were involved in the pathogenesis of CVC, including genetic, mechanical, biochemical, and therapeutic factors. Several polymorphisms and products of genes such as lipoprote A gene and Notch gene play a role in the process of aortic valve calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Valvular disease in patients with CKD is accelerated by comorbidities like diabetes, arterial hypertension, hyperlipidemia, anemia and ongoing infections of valves, and malnutrition, as well as hypercalcemia, hyperphosphatemia, and hyperparathyroidism. 85 …”
Section: Pathophysiology Of Cvd In Ckdmentioning
confidence: 99%